Albendazole-induced associated acute hepatitis and bicytopenia. (February 2014) - Ben Fredj, Nadia; Chaabane, Amel; Chadly, Zohra; Ben Fadhel, Najeh; Boughattas, Naceur A.; Aouam, Karim
Abstract Acute hepatitis induced by albendazole is rarely reported. We describe herein an original case of acute hepatitis associated with bicytopenia after albendazole intake. This paper is the first to describe a possible association of a hematologic disorder and acute hepatitis, both induced by albendazole therapy.